Do different habitat preference survey methods produce the same conservation recommendations for lesser kestrels? - Franco, a M. a; Catry, I.; Sutherland, W. J.; Palmeirim, J. M. (Animal Conservation, 2004)
The analysis of habitat selection underlies many conservation recommendations. Different researchers use different methods, therefore there is a need to examine whether the results are consistent. This study examined habitat selection by lesser kestrels, Falco naumanni, a globally threatened species, using two methods: visual sighting data from a 35-km transect and radio-telemetry of 33 birds. Habitat use and spatial ecology were studied across all of the breeding season in a pseudo-steppe area, where traditional agro-grazing systems are still present but some areas have been transformed into pine plantations. Telemetry data indicate that, in good quality habitat, lesser kestrels prefer to forage close to the colony. Furthermore, the home ranges obtained were smaller than those for lesser kestrels using intensively managed habitats or more forested areas. Habitat availability was determined within a 4-km radius of the colony and habitat preferences were determined using compositional analysis. Both methods were found to produce similar results, but telemetry provided a larger number of signiﬁcant differences between habitats. Before the chicks hatched, lesser kestrels preferred grazed fallows, ploughed ﬁelds and cereal, while after hatching cereal stubble was the preferred habitat. In steppe habitats the protection of such foraging habitats within a 3-km radius from the colonies could be a very effective conservation measure.
Keywords: habitat selection; Lesser kestrel; spatial ecology (PG)